Comparison of oral ampicillin and doxycycline in the treatment of uncomplicated gonorrhoea. Issue 2 (April 1975) - Enfors, W; Eriksson, G
Abstract : An account is given of a computer-processed 1-year study comprising 1, 124 patients (625 males and 499 females) with uncomplicated gonorrhoea. Alternate patients were treated with either two oral doses of 1 g. ampicillin 5 hours apart, or 0.3 g. doxycycline in a single oral dose. Ampicillin remained as efficacious as in 1968 to 1970, in both males and females, in whom the failure rates were 1.1 and 1 per cent. respectively. After doxycycline the failure rate was 8.1 per cent. in males, 5.7 per cent. in females, and 7.1 per cent. overall. Ampicillin was significantly better than doxycycline in the treatment of men (P less than 0.001) as well as of women (0.05 greater than P greater than 0.01). 89.7 per cent. (29/29) of the relapses in doxycycline-treated patients occurred in those harbouring strains sensitive to tetracycline. Sensitivity to doxycycline followed the pattern of tetracycline sensitivity. Thus sensitivity tests with these antibiotics provided no practical aid to therapy. The high incidence of nausea and vomiting in patients treated with doxycycline (12 per cent.) makes it inadvisable to increase the dose; instead, multiple doses are necessary to obtain satisfactory results. There were very few adverse reactions to ampicillin; a rash occurred in only three patients (0.5 per cent.). In the group treated with doxycycline, 31.5 per cent. of the patients infected by streptomycin-resistant strains relapsed compared with only 1.8 per cent. of patients infected by streptomycin-sensitive strains. This difference is highly significant (P less than 0.001). Thus the sensitivity of gonococcal strains to streptomycin in vitro may serve as a valuable guide to the likely outcome of treatment with tetracyclines.